IMPROVING THE TECHNOLOGY OF CUPCAKES WITH THE USE OF LUPINE FLOUR - KOSHEL, OLENA; SAVCHENKO, MARINA; PERCEVOY, FEDOR; MARENKOVA, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article is devoted to improving the technology of cupcakes by introducing lupine flour into their recipe. Lupine flour has been determined to be free of cholesterol, gluten and stomach irritants; modern sweet varieties do not contain alkaloids. Due to its low starch content and high dietary fiber content, it has a very low glycemic index (GI) and is recommended as an element in the diet of diabetics or people who want to lose weight, lower blood cholesterol and triglycerides and regulate blood pressure.Lupine flour contains up to 40% protein. Its fractional composition contains salt- and water-soluble proteins - 82-85%, alkali-soluble - 5-8%, insoluble fraction - 9-10%, alcohol-soluble proteins are completely absent. In terms of amino acid composition, lupine protein has a high content of lysine, threonine and leucine compared to other proteins contained in legumes. These amino acids have a positive effect on the young body (lysine and threonine) and are used in the treatment of diseases such as liver disease and anemia (leucine).In the work, 3 samples of cupcakes were developed with a partial replacement of wheat flour with lupine flour. After baking, samples with the addition of lupine flour were determined by organoleptic quality indicators, namely taste, smell, shape, texture, surface, structure and cross-sectional view. Research data showed that the addition of lupine flour in the amount of 15.0%...30.0% significantly improved the texture of the muffins compared to the control sample. The sample of the cake with a partial replacement of wheat flour with lupine flour meets the requirements of a healthy diet to the greatest extent due to the increased content of proteins (22.83%) and the reduced content of carbohydrates (36.33%).In general, the analysis of the chemical composition according to the content of proteins, fats, and carbohydrates showed the advantage of the improved recipes of the "Stolichny" cake, in particular, according to the content of the amino acid composition of proteins and fats, as well as reduced calorie content.Based on the results of the research, it can be concluded that the improved muffins expand the assortment of flour confectionery products for healthy nutrition with the content of essential amino acids in their optimal ratio.
Keywords: flour confectionery; cupcakes; lupine flour; amino acid composition; proteins; nutritional value; healthy food